Dispelling the Ghost:: Iraq as the Vietnam War We Cannot Afford to Lose - Lomperis, Timothy (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2006)
ABSTRACT As the war in Iraq lengthens, references to it as another Vietnam have increased. But Vietnam today is more of a ghost than a reality of what it was 30 years ago. As a ghost, Vietnam carries a haunting message of defeat for Western interventions in "third world wars." Despite some dangerous parallels, this message is wrong in that the American defeat in Vietnam was largely a self-inflicted wound. Further, the geopolitics of the War on Terror and its strategy of preemption (as opposed to the Cold War and its policy of containment), has fused the war in Iraq with the battle against al-Qaeda to the point where Iraq has become the struggle from which Americans cannot walk away — as they did in Vietnam.